Shared Psychotic Disorder in Old Age: Syndrome of Folie à Deux - Schopfer, Q.; Eshmawey, M. (Case Reports in Psychiatry, 2022)
Background. Shared psychotic disorder is a relatively rare condition first described by Lasegue and Falret in 1877, who named the syndrome “folie à deux” (FAD). This disorder is characterized by the transference of delusional ideas from one individual to another. Methods. We report the case of a mother and daughter who exhibited shared delusions of persecution after living in near-total isolation for 10 years. Both patients were hospitalized in two different wards, and the combination of separation, supportive, and pharmacological therapy resulted in remission for the mother and partial remission for the daughter. Results. Both patients were discharged, and a network was created by the psychiatric hospital which activated social workers for outpatient care. We also planned outpatient psychiatric sessions focused on the patients’ specific role in the folie à deux disease, led by two different psychiatrists. Conclusion. FAD has a long history but it is still an unconventional psychiatric diagnosis. This case report sheds light on the clinical features and how to set proper treatment strategies. While the phenomenon of FAD in old age may not be as rare as previously thought, the literature remains scarce.